Comparison of daily versus nondaily image‐guided radiotherapy protocols for patients treated with intensity‐modulated radiotherapy for head and neck cancer. Issue 7 (27th November 2013) - Yu, Yao; Michaud, Anthony L.; Sreeraman, Radhika; Liu, Tianxiao; Purdy, James A.; Chen, Allen M.
Abstract Background The purpose of this study was to determine the feasibility of nondaily image‐guided radiotherapy (RT) strategies with intensity‐modulated radiotherapy (IMRT) for head and neck cancer. Methods Alignment data was analyzed from 103 consecutive patients treated by IMRT for head and neck cancer who had undergone daily imaging with onboard mega‐voltage CT (MVCT), resulting in 3275 images. Geometric setup errors that would have occurred using less‐than‐daily imaging were hypothetically estimated for 4 temporal less‐than‐daily image‐guided RT protocols. Results For image‐guided RT on the first fraction, weekly image‐guided RT, first 5 + weekly image‐guided RT, and alternating day image‐guided RT, the respective incidences of geometric miss were 50.5%, 33.8%, 30.1%, and 15.7% assuming 3‐mm uncertainty margins; and 18.7%, 11.7%, 10.3%, and 4.1% with 5‐mm margins. Conclusion Less‐than‐daily image‐guided RT strategies result in a high incidence of potential miss when 3‐mm uncertainty margins are utilized. Less‐than‐daily image‐guided RT strategies should incorporate margins of at least 5 mm. © 2013 Wiley Periodicals, Inc. Head Neck 36: 992–997, 2014